Rural research in the humanities and social sciences II proceedings of the second annual clloquium of the rural research centre, NSAC (Nova Scotia Agricultural College/ Rural Research Centre, 1995)
Rural areas serve as reservoirs of resources, natural and social, as mediating pathways between the urban and the wild, and as arenas for everyday life. It is imperative that rural research address change in the countryside and work toward a better understanding of rurality in the late twentieth century and into the new millenium. The Rural Research Centre at the Nova Scotia Agricultural College exists to provide a focus for scholarly rural research in theHumanities and Social Sciences. To accomplish this the main roles of the Rural Research Centre are to encourage and facilitate communications through meeting--conferences, colloquia, lectures--and publications. Additionally, the Rural Research Centre will endeavour to support research programs and projects, and serve as a networking facilitator, helping to connect scholars and students with other interested individuals and groups. In short, the Rural Research Centre will try to foster scholarly research on rural themes and issues, with an emphasis on, but not a limitation to, the Atlantic region of Canada.